Understanding the theoretical underpinning of the exercise component in a fall prevention programme for older adults with mild dementia: a realist review protocol - Booth, Victoria; Harwood, Rowan H.; Hood, Victoria; Masud, Tahir; Logan, Phillipa A. (BioMed Central, 2016)
Background